Estrogen Effects in Psychiatric Disorders - Bergemann, Niels; Riecher-Rössler, Anita (Springer-Verlag/Wien, 2005)
The study of the effects of gonadal hormones in the brain focussed mainly on reproductive actions for a long time. Meanwhile, however, it is well known that gonadal hormones, in particular estrogens, also have neuroprotective and psychoprotective properties. They modulate many brain functions such as cognitive functions, pain regulation, motor coordination, and epilepsy, as well as affective and psychotic disorders, to name just a few. In fact, during the past few years we have experienced a major change in our understanding of the endocrinologic aspects of psychiatric disorders. Endocrinologic irregularities in psychiatric patients are no longer viewed as pure epiphenomena but rather discussed as part of the pathomechanism of the disorders. How exactly estrogens affect various disorders is a fascinating and intriguing aspect of this emerging field of non-reproductive brain actions of gonadal hormones. Among the estrogens, especially estradiol appears to play an important and multimodal role in the brain. Which of estradiol's many membrane, intracellular, and genomic actions matters most in psychiatric disorders, remains to be discovered. The aim of this volume is to summarize the role estrogens play in major psychiatric disorders, such as schizophrenia, depression, and dementia, and to provide a state-of-the-art overview of current knowledge, but also of questions that are still open. It is intended to be a resource for clinicians and readers who are interested in contemporary research developments in this field.
Includes bibliographical references
Keywords: Aufsatzsammlung; Östrogene; Psychische Störung; Alzheimerkrankheit; Depression; Schizophrenie